Nuclear weapons and explosions environmental impacts and other effects - Yadav, M. S. (SBS, 2007)
Covers the area of major impacts of nuclear weapons and explosions in its totality and gives a detailed fact sheet on nuclear weapons and accidents. A nuclear weapon derives its destructive force from nuclear reactions of fission or fusion, thus making even a nuclear weapon with a relatively small yield significantly more powerful than the largest conventional explosives. Consequently, a single weapon is capable of destroying an entire city like Hiroshima. Nuclear explosives have been tested and used for various non-military uses. Nuclear explosions produce both immediate and delayed destructive effects such as blasts and radioactive fallout. The impacts and injuries caused by nuclear blasts and resulting radiation effects causing cancer, congenital defects, mental retardation, immune destruction, cancer, stillbirths and other health problems is discussed in detail. Besides the blast and radiation damage from individual bombs, a large scale nuclear exchange between nations could conceivably have a catastrophic global effect on climate and pollute vast amounts of soil and water. The Book is divided into seven chapters and is a must read for all concerned with nuclear safety.